Design of two basketball teaching programs in two different teaching methods - Sergio González Espinosa; Sergio José Ibáñez Godoy; Sebastian Feu Molina (Federación Extremeña de Balonmano; University of Extremadura, 2017)
Sport is used by physical education teachers as part of their classes. Students are influenced by teaching methods. There are two general approaches, one focused on the teacher (Teacher-Centered Approach) and another focused on students (Student-Centered Approach). The objective of this study is to design and analyze two intervention programs, one with the Direct Instruction and another with the Tactical Game Approach. The sample was composed by 40 tasks. The variables used in the research were classified as pedagogical variables and external load variables. The analysis of the tasks was made with the "Sistema Integral de Análisis de las Tareas de Entrenamiento". To compare both programs, the Chi-square, Mann-Whitney U test and independent sample t was used according to data nature. To identify the category of the variable that differentiates both programs, the Corrected Standard Waste was used. Furthermore, the strength of association with Cramer's Phi (φc), Cramer's V (Vc) and Kendall's Tau-c was calculated. The programs are homogeneous in variables determined by the design of tasks. On the other hand, they are different in variables that are determined by the identity of each methodology.